Water Management during the Dacian Period in the Orăştie Mountains. Catchment and Storage of Water - VASILACHE, Ștefan (Studia Universitatis Babeș-Bolyai Historia, 2021)
The purpose of this article is to offer a general view over the different systems of catchment and storage of water used during the Dacian antiquity in the Orăştie Mountains area, Romania. The methodology will be based on a dichotomous approach, in an effort that tries to compare the hydrological situation (supported by GIS maps) with the known archaeological discoveries relevant for the subject. Rezumat: Scopul articolului este de a oferi o imagine generală asupra diferitelor sisteme de captare şi depozitare a apei folosite de dacii care locuiau în antichitate zona munţilor Orăştiei. Metodologia se va baza pe o abordare în oglindă, anume interpretarea diferitelor descoperiri arheologice relevante în funcţie de situaţia hidrografică specifică (pe baza unor hărţi GIS). Cuvinte-cheie: apă, captare, stocare, cisterne, hidrografie, GIS, daci.